2020
DOI: 10.1108/jpbafm-05-2020-0059
|View full text |Cite
|
Sign up to set email alerts
|

Time to rethink public sector accounting education? A practitioner’s perspective

Abstract: PurposePublic sector accounting (PSA) education has recently become the focus of scholars and practitioners alike. The article aims to reflect on PSA education from a practitioner’s perspective. Based on the author's experiences with accounting change projects in the public sector and teaching PSA education at different higher education institutions (HEIs) and levels, possible implications are derived for PSA education.Design/methodology/approachThe article represents a viewpoint by a practitioner. Examples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The uptake of accrual accounting by national and local governments has significantly increased in recent years. So there is a clear need to educate public servants on accrual accounting in the public sector (Adam et al, 2019;Heiling, 2020;Cohen & Karatzimas, 2022) (Polzer et al, 2022) raises interesting thoughts on the relation between PSAE and the harmonization of public sector accounting practices. When choosing between multiple standards (for example IPSASs or EPSASs), countries will prefer an adaptation of the standards that best fit their national practices and local needs, which challenges PSAE to simultaneously address internationally harmonized public sector accounting and not to ignore local standards and practices.…”
Section: Psae Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…The uptake of accrual accounting by national and local governments has significantly increased in recent years. So there is a clear need to educate public servants on accrual accounting in the public sector (Adam et al, 2019;Heiling, 2020;Cohen & Karatzimas, 2022) (Polzer et al, 2022) raises interesting thoughts on the relation between PSAE and the harmonization of public sector accounting practices. When choosing between multiple standards (for example IPSASs or EPSASs), countries will prefer an adaptation of the standards that best fit their national practices and local needs, which challenges PSAE to simultaneously address internationally harmonized public sector accounting and not to ignore local standards and practices.…”
Section: Psae Challengesmentioning
confidence: 99%
“…On the other hand, the academic literature has highlighted the growing complexities of public sector accounting, and its interdisciplinarity within the public financial management framework (Caruana et al, 2019;Heiling, 2020). The demand for cross-disciplinary knowledge by public sector accounting professionals raises important challenges for PSAE.…”
Section: Psae Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation related to the awareness of the world of work noted several implications for accounting education [8]. The necessity to employ digital technology in accounting education is justified by the fact that graduates emerging from business schools will enter a workplace abundant in technology Accounting education in this environment carries a greater responsibility and plays a crucial function as it must equip graduates with the ability to effectively adjust to the evolving needs of the labor market.…”
Section: Introductionmentioning
confidence: 99%
“…Since reforms and changes have taken place in PSA, including the implementation of new accounting basis and additional reports, higher education institutions (HEIs) should recognize the need to improve education in the field of PSA, because PSA and related education should go hand in hand (Heiling, 2020). Previous studies have shown that HEIs were not focused on the public sector (Adam et al, 2019), so there is a gap in knowledge caused by inadequate formal university education of students (Chan, 2022).…”
Section: Introductionmentioning
confidence: 99%